The Impact of Palliative Transurethral Resection of the Prostate on the Prognosis of Patients With Bladder Outlet Obstruction and Metastatic Prostate Cancer: A Population-Matched Study - Fang, Kun; Song, Pan; Zhang, Jiahe; Yang, Luchen; Liu, Peiwen; Lu, Ni; Dong, Qiang (Frontiers in Surgery, 2021)
Objective: This study aimed to evaluate the survival outcomes of patients with bladder outlet obstruction (BOO) and metastatic prostate cancer (mPCa) after having a palliative transurethral resection of the prostate (pTURP) surgery. Methods: We identified patients with mPCa between 2004 and 2016 in the Surveillance, Epidemiology, and End Results (SEER) database. Patients who received pTURP and non-surgical therapy were identified. A propensity-score matching was introduced to balance the covariate. Kaplan–Meier analysis and COX regression were conducted to evaluate the overall survival (OS) and cancer-specific survival (CSS) outcomes. Results: A total of 36,003 patients were identified; 2,823 of them were in the pTURP group and 33,180 were in the non-surgical group. The survival curves of the overall cohort showed that the pTURP group was associated with worse outcomes in both OS (HR: 1.12, 95% CI: 1.07–1.18, p < 0.001) and CSS (HR: 1.08, 95% CI: 1.02–1.15, p = 0.004) compared with the non-surgical group. The mean survival time in the overall cohort of the pTURP group was shorter than the non-surgical group in both OS [35.13 ± 1.53 vs. 40.44 ± 0.59 months] and CSS [48.8 ± 1.27 vs. 55.92 ± 0.43 months]. In the matched cohort, the pTURP group had significantly lower survival curves for both OS (HR: 1.25, 95% CI: 1.16–1.35, p < 0.001) and CSS (HR: 1.23, 95% CI: 1.12–1.35, p < 0.001) than the non-surgical group. pTURP significantly reduced the survival months of the patients (36.49 ± 0.94 vs. 45.52 ± 1.23 months in OS and 50.1 ± 1.49 vs. 61.28 ± 1.74 months in CSS). In the multivariate COX analysis, pTURP increased the risk of overall mortality (HR: 1.19, 95% CI: 1.09–1.31, p < 0.001) and cancer-specific mortality CSS (HR: 1.23, 95% CI: 1.14–1.33, p < 0.001) compared with the non-surgical group. Conclusions: For mPCa patients with BOO, pTURP could reduce OS and CSS while relieving the obstruction.